Active fly ash-based catalyst, preparation thereof and application of active fly ash-based catalyst in liquid-phase advanced oxidative degradation of organic pollutants

By combining alcohol-base-assisted mechanical ball milling and low-temperature alkali melting, fly ash is activated, and the problem of insufficient activation degree and high cost of fly ash is solved, and active fly ash catalysts are obtained with high activity, broad spectrum and stability, achieving efficient oxidation and degradation of organic pollutants.

CN119588356AActive Publication Date: 2025-03-11EAST CHINA UNIV OF SCI & TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411702271.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In the prior art, fly ash is used as a catalyst carrier, and the activation degree is insufficient, the activation process is complex, the cost is high, the pollution is serious, and the Si and Al components in fly ash are not fully resourced.

Method used

The activation method of combining alcohol-base-assisted mechanical ball milling and low-temperature alkali melting is adopted, and the ball milling of fly ash with ethanol and sodium hydroxide is mixed, and then melt-calcined to form a fly ash catalyst with a high activity and porous structure.

Benefits of technology

Deep activation of fly ash is achieved, and active fly ash catalyst with high activity, broad spectrum and stability is obtained, which can efficiently oxidize and degrade organic pollutants, reducing preparation costs and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588356A_ABST
    Figure CN119588356A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemistry and chemical engineering technology and environmental protection, and relates to an active fly ash-based catalyst and preparation and application thereof in liquid-phase advanced oxidative degradation of organic pollutants, the raw materials of the catalyst comprise a fly ash raw material, an alkali activator and alcohol, the mass ratio of the fly ash raw material to the alcohol is (0.5-10): 1, and the alkali activator is an alkali activator. The mass ratio of the fly ash raw material to the alkali activator is (0.1-5.0): 1. The preparation method mainly comprises two combined steps of alcohol-alkali ball milling and low-temperature melting, that is, firstly, fly ash is subjected to mechanical ball milling treatment in the presence of a certain amount of alkali and short-chain alcohol, and then the active fly ash catalyst is prepared through the steps of low-temperature melting roasting, washing, drying and the like. Compared with the prior art, the fly ash-based catalyst provided by the invention has the characteristics of greenness, high efficiency, mild conditions, simple process and easy large-scale production, other active metal components do not need to be additionally introduced into the activated fly ash, the cost is low, and the prepared catalyst also has the advantages of high activity, broad spectrum, good stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical engineering technology and environmental protection, and relates to a method for preparing an active fly ash-based catalyst. The catalyst obtained by the invention can be used for liquid phase advanced oxidation degradation and mineralization of organic pollutant waste gas and waste water. Background Art

[0002] Fly ash refers to the fine ash particles collected from flue gas during coal combustion, and its main components are Si, Al and Fe. The reuse or resource conversion of fly ash has significant social and economic benefits in environmental pollution control, resource and energy conservation, and high-value product development.

[0003] Fly ash has a large structural polymerization degree, high bond energy, stable chemical properties at room temperature, and low activity. Therefore, the research on fly ash activation has become a hot spot in the current fly ash application research. Common methods of fly ash activation include mechanical activation, chemical activation, and thermal activation. (1) Mechanical activation, which improves the activity of fly ash by increasing the fineness of fly ash. There are two main types of processing: sorting and grinding. Sorting is to group fly ash particles according to their size. It has low energy consumption, high efficiency, and low noise, but it does not change the morphology of fly ash particles or destroy the surface structure of spherical glass, and has low utilization rate. Grinding is to refine fly ash particles, increase the degree of structural irregularity and defects, and increase the chemical energy of fly ash particles, increase their chemical instability, and increase their activity. (2) Chemical activation refers to the combination of SiO2 or Al2O3 in fly ash with Ca(OH)2 under the action of activators, mainly alkaline activators or sulfate activators, to form gel products such as calcium silicate hydrate (CSH) or calcium aluminate hydrate (CAH). (3) Thermal activation, which changes the composition and physical structure of fly ash by calcination or autoclaving to improve its activity. The advantage is that it can be used in prefabricated and cast-in-place components like cement, but it consumes a lot of energy, has high investment costs, and long-term storage may lead to loss of activity.

[0004] Patent CN118079917 A provides a method for preparing a catalytic material based on fly ash in the field of denitrification. First, the magnetic material in the fly ash substrate is selected by wet slag magnetic separation, and then oxygen-enriched ball milling is performed with hydrogen peroxide as an auxiliary agent. The collision and friction between the material particles activate and generate surface oxygen vacancies. Finally, plasma discharge modification is performed by passing oxygen to obtain a catalytic material with rich oxygen vacancies and high redox activity on the surface. Similarly, patent CN116586062 A provides a method for preparing a high electron transfer catalytic material based on fly ash. However, the entire preparation process involves multiple steps such as wet slag magnetic separation, oxygen-enriched high-energy ball milling, and plasma discharge, which require high costs such as equipment, energy, and chemical reagents. In addition, the invention only reuses magnetic materials such as iron in fly ash, while more Si and Al components are not fully resourced.

[0005] Patent CN117899908 A discloses a catalyst with fly ash as carrier, its preparation method and application. The catalyst is composed of fly ash carrier and N-doped copper-aluminum bimetallic oxide active component loaded on the carrier. It has high catalytic efficiency and wide pH application range for treating organic wastewater. However, in this invention, fly ash is only used as a carrier of the catalyst, and the fly ash has not undergone deep activation treatment except for simple acid solution soaking and washing pretreatment, and the utilization efficiency of fly ash is low. Patent CN109046298 A discloses a modified fly ash with adsorption and catalytic functions, its preparation method and application. The prepared modified fly ash not only has strong adsorption capacity for heavy metals and large adsorption capacity as an adsorbent, but also can catalyze Fenton reaction and promote the degradation of organic pollutants in soil. However, in this invention, the alkali melting temperature of fly ash is high and an active Fe component needs to be added.

[0006] In the existing patents, fly ash is mainly used as a catalyst carrier when used as a raw material to prepare high value-added functional materials, especially catalytic materials. In the actual process, other active components must be introduced. In addition, the activation degree of fly ash is insufficient and not fully activated, or there are problems such as complex activation process, high cost, serious pollution, and cumbersome experimental operation. Therefore, it is of great significance to develop a green, low-cost fly ash-based catalyst preparation method, especially a catalyst with high activity itself, for the resource utilization of fly ash. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide an active fly ash-based catalyst with high activity, broad spectrum and good stability, as well as its preparation and application in liquid phase advanced oxidation degradation of organic pollutants.

[0008] The purpose of the present invention can be achieved by the following technical scheme: an activated fly ash-based catalyst, the raw materials of the catalyst include fly ash raw material, alkali activator and alcohol, wherein the mass ratio (solid-liquid ratio) of the fly ash raw material to the alcohol is 0.5-10:1, and the mass ratio of the fly ash raw material to the alkali activator is 0.1-5.0:1.

[0009] Furthermore, the mass ratio of the fly ash raw material to the alcohol is 2-6:1, and the mass ratio of the fly ash raw material to the alkali activator is 0.1-2:1.

[0010] Furthermore, the fly ash raw material is industrial waste fly ash from coal-fired power plants, which is solid waste fly ash collected from flue gas emitted from the combustion of pulverized coal, and usually has an Fe content higher than 0.5%, and does not require other pretreatment.

[0011] Furthermore, the alcohol is a short-chain alcohol, a low-carbon fatty alcohol with 1 to 4 carbon atoms and a combination thereof, including methanol, ethanol, propanol or butanol, preferably ethanol.

[0012] Furthermore, the alkaline activator includes one or more of oxides, peroxides, hydroxides and carbonates of alkali metals and alkaline earth metals, preferably sodium hydroxide.

[0013] The present invention also provides a method for preparing an activated fly ash-based catalyst, comprising the following steps: mixing a fly ash raw material with an alkali activator and an alcohol and placing the mixture in a ball mill for mechanical ball milling, then melt-calcining the fly ash after the ball milling, washing the obtained product until the pH value is close to neutral, and drying the product to obtain an activated fly ash-based catalyst.

[0014] Furthermore, the mechanical ball milling conditions are as follows: the ball milling frequency is 100-700 Hz, preferably 500 Hz, and the ball milling time is 1-5 h, preferably 2.5 h;

[0015] The melt roasting conditions are as follows: the roasting temperature is 200-800°C, preferably 450°C, and the roasting time is 0.5-5h, preferably 4h.

[0016] Furthermore, the washing is performed using deionized water or a dilute acid solution.

[0017] The present invention also provides an application of an activated fly ash-based catalyst, wherein the catalyst is used to treat wastewater containing organic pollutants, specifically comprising the following steps:

[0018] First, a certain amount of the activated fly ash catalyst is added to the wastewater containing organic pollutants, stirred, adjusted to an appropriate pH value and temperature, and then an oxidant is added. After a certain reaction time, the concentration of organic pollutants is determined by liquid chromatography and the conversion efficiency is calculated. For organic pollutant waste gas, it can be introduced into deionized water by bubbling, etc., and the other steps are the same as wastewater treatment.

[0019] Furthermore, the organic pollutant may be one or more of chlorinated organic compounds such as o-chlorophenol and chlorobenzene, phenol, bisphenol A, o-aminophenol, and the like.

[0020] Furthermore, the amount of the activated fly ash catalyst is 100-1000 mg / L, preferably 400 mg / L.

[0021] Furthermore, the oxidant is selected from at least one of hydrogen peroxide, peracetic acid, persulfate, permonosulfate and ozone, preferably hydrogen peroxide.

[0022] Furthermore, the dosage of the hydrogen peroxide is 0.1-10 ml / L, preferably 3 ml / L.

[0023] Furthermore, the oxidation temperature is 5-60°C, preferably 40°C.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] 1. The present invention innovatively adopts an activation method combining alcohol-alkali assisted mechanical ball milling and low-temperature alkali melting, which can transform the stable crystalline phase structure of fly ash into an amorphous phase, obtain a larger surface area and a richer pore structure, and the activation process has the advantages of simple process, low cost, low energy consumption, and low environmental pollution.

[0026] 2. In the present invention, Fe, Si, Al and other elements in the fly ash will be recombined in situ during the activation process to form bulk-stable and highly dispersed Fe active species, directly converting the fly ash into an active fly ash catalyst with catalytic activity, thereby eliminating the need to introduce other active metals, shortening the preparation process of the fly ash-based catalyst and reducing costs.

[0027] 3. The activated fly ash catalyst provided by the present invention has an active component that is in situ and highly dispersed and stabilized in the porous, large-surface-area bulk structure of the activated fly ash, thereby improving the activity and stability of the Fe active component, enabling it to react with an oxidant to generate free radicals, which oxidize low-concentration organic pollutants, thereby achieving efficient and stable catalytic oxidation of organic pollutants. At the same time, due to the mild reaction conditions and the indiscriminate oxidation of free radicals, the complete removal of difficult-to-degrade organic matter in wastewater, such as o-chlorophenol, can be ensured.

[0028] 4. In view of the deficiencies in the prior art, the present invention provides a mild and green method for activating fly ash to prepare an active fly ash catalyst for advanced oxidation degradation of organic pollutants in waste gas and wastewater, which solves the current problems of low-end application (only as a carrier), complicated process, high cost, waste of resources and serious environmental pollution in the reuse of fly ash as a catalytic material. It transforms fly ash from solid waste into a catalytic material with high catalytic activity. It not only solves the problems of fly ash storage and pollution, but also provides ideas for increasing the added value of fly ash utilization.

[0029] 5. The fly ash-based catalyst preparation method provided by the present invention can deeply destroy the original fly ash high-temperature sintering phase with low surface area, high density, difficult to shape, and no catalytic activity, and make it porous and amorphous, and generate an active phase in situ. It has the characteristics of green and high efficiency, mild conditions, simple process and easy scale-up. The activated fly ash does not need to introduce other active metal components and has low cost. The prepared catalyst also has the advantages of high activity, broad spectrum, good stability, etc., and has broad industrial application prospects. In addition, the present invention has good social and economic benefits in promoting the resource reuse of industrial solid waste fly ash, turning waste into treasure, and treating waste with waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the SEM spectrum of the original fly ash in Example 1;

[0031] Figure 2 This is the SEM spectrum of the fly ash catalyst product after activation treatment in Example 1. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0033] In conjunction with the accompanying drawings, some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.

[0034] In the following embodiments, if there is no special description of raw materials or processing technology, it means that they are all conventional commercially available raw materials or conventional processing technologies in the field. If there is no special description of functional components or structures, it means that they are all conventional components or conventional structures used in the field to achieve corresponding functions.

[0035] Example 1

[0036] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0037] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0038] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0039] Figure 1 This is the SEM spectrum of the original fly ash in Example 1. Figure 2 This is the SEM spectrum of fly ash after activation treatment in Example 1. Figure 1 It can be seen that the original fly ash is mainly spherical, consisting of microspheres, irregularly shaped debris and porous particles (unburned carbon). Microspheres are hollow spheres formed during the combustion process, and the particle size is uneven. Figure 2 It can be seen that the original fly ash becomes broken after high-alkali ball milling and high-temperature melting operations. The spherical structure of the original fly ash breaks into small fragments, the specific surface area increases, and the active sites increase.

[0040] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0041] Example 2

[0042] Step 1: 10 g of fly ash raw material from power plant B, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0043] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0044] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0045] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0046] Example 3

[0047] Step 1: 10 g of fly ash raw material from power plant C, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0048] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0049] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0050] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0051] Example 4

[0052] Step 1: 10 g of fly ash raw material from power plant D, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0053] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0054] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0055] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0056] Example 5

[0057] Step 1: 10 g of fly ash raw material from E power plant, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0058] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0059] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0060] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0061] Comparative Example 1

[0062] The fly ash raw material from power plant A in Example 1 was directly added to simulated wastewater containing 200 ppm of o-chlorophenol, and the detection was carried out using the same method as in Example 1.

[0063] The main components of fly ash raw materials from different power plants in Examples 1-5 are shown in Table 1 below:

[0064] Table 1 List of main components of original fly ash of Examples 1 to 5

[0065] Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[SiO2]]> 40.26% 38.79% 41.55% 42.24% 35.87% <![CDATA[Al2O3]]> 32.90% 29.86% 22.52% 29.86% 30.92% <![CDATA[Fe2O3]]> 2.90% 3.41% 7.64% 3.59% 4.91% .

[0066] The activity test results of each embodiment and comparative example are shown in Table 2 below. Compared with the original fly ash, the activated fly ash catalyst prepared by the present invention shows significant activity for the advanced oxidation degradation of o-chlorophenol, and the degradation rate of o-chlorophenol is as high as 99% or more after 30 minutes of reaction. In addition, fly ash from different power plants (the main components of fly ash are shown in Table 1) all show high catalytic activity after the activation treatment of the present invention, and the method of the present invention has universality.

[0067] Table 2 Activity data table of Examples 1 to 5

[0068]

[0069]

[0070] Example 6

[0071] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of water, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz and ball milling time of 2.5 h);

[0072] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0073] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0074] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0075] Example 7

[0076] Step 1: 10 g of fly ash raw material from power plant A and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for dry ball milling (ball milling frequency of 500 Hz and ball milling time of 2.5 h);

[0077] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0078] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0079] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0080] Example 8

[0081] Step 1: 10 g of fly ash raw material from power plant A and 12 g of NaOH were directly placed in a crucible for melting and roasting at a temperature of 450 ° C for 4 h;

[0082] Step 2: Wash the solid calcined in step 1 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0083] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0084] Table 3 Activity data table of Example 1, Example 6 to Example 8

[0085]

[0086] The activity test results in Table 3 above show that the degradation rate of o-chlorophenol by activated fly ash obtained by using different solvents to assist in the ball milling of fly ash is different, especially the degradation efficiency at 10 minutes of reaction. The activity effect of ethanol, sodium hydroxide and fly ash mixed and then ball milled and roasted is the best. Nevertheless, after 30 minutes of reaction, the degradation rate of o-chlorophenol can reach more than 98%. This shows that the reason why the activity of fly ash is greatly improved after high-alkali ball milling and melting is mainly due to the increase in the surface area and pore structure of fly ash and the possible in-situ reconstruction of active phases.

[0087] Example 9

[0088] Step 1: 10 g of fly ash raw material from power plant A, 1 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0089] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0090] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0091] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0092] Example 10

[0093] Step 1: 10 g of fly ash raw material from power plant A, 10 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0094] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0095] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0096] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0097] Table 4 Activity data table of Example 1, Example 9, and Example 10

[0098] Example 1 Example 9 Example 10 Adsorption rate (30min) 10.4% 9.7% 9.2% Degradation rate (10min) 86.3% 80.2% 70.5% Degradation rate (30min) 99.6% 98.7% 96.3%

[0099] The activity test results in Table 4 above show that the degradation rate of o-chlorophenol by activated fly ash obtained by using different amounts of ethanol in the fly ash ball milling process is different. Too little ethanol leads to insufficient dissolution of sodium hydroxide, and too much ethanol easily forms sodium ethoxide. Too much or too little ethanol has an effect on the activity of fly ash. The optimal value of ethanol is 2.5 ml between 1 ml and 10 ml.

[0100] Embodiment 11

[0101] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0102] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 300° C. for 4 h;

[0103] Step 3: The solid calcined in step 2 is dispersed in a deionized water bath at 50° C. and heated and stirred for 4 hours, and then washed with deionized water until the pH value is close to neutral, and then dried to obtain an active fly ash catalyst.

[0104] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0105] Example 12

[0106] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0107] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 500° C. for 4 h;

[0108] Step 3: The solid calcined in step 2 is dispersed in a deionized water bath at 50° C. and heated and stirred for 4 hours, and then washed with deionized water until the pH value is close to neutral, and then dried to obtain an active fly ash catalyst.

[0109] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0110] Embodiment 13

[0111] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0112] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 900° C. for 4 h;

[0113] Step 3: The solid calcined in step 2 is dispersed in a deionized water bath at 50° C. and heated and stirred for 4 hours, and then washed with deionized water until the pH value is close to neutral, and then dried to obtain an active fly ash catalyst.

[0114] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of o-chlorophenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the o-chlorophenol concentration in the solution was determined after stirring and adsorption for 30 minutes; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of o-chlorophenol in the solution was determined after the reaction for 10 minutes and 30 minutes, respectively. The concentration of o-chlorophenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0115] Table 5 Activity data table of Example 1, Example 11 to Example 13

[0116] Example 1 Embodiment 11 Example 12 Embodiment 13 Adsorption rate (30min) 10.4% 13.17% 10.48% 11.61% Degradation rate (10min) 86.3% 19.89% 54.80% 23.43% Degradation rate (30min) 99.6% 74.33% 99.33% 98.27%

[0117] The activity test results in Table 5 above show that the catalyst activity obtained by calcining the fly ash carrier after ball milling at different temperatures is different. When the temperature is lower than 450°C, the catalyst activity decreases, which may be because the calcination temperature is low, the sodium hydroxide is not completely melted, and the etching degree of the fly ash is insufficient. When the temperature is 500°C, the final degradation rate is similar to that at 450°C. When the temperature is as high as 900°C, the active phase sinters, resulting in a decrease in the degradation rate.

[0118] Embodiment 14

[0119] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0120] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0121] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0122] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of phenol, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the mixture was stirred and adsorbed for 30 minutes, and the concentration of phenol in the solution was measured; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of phenol in the solution was measured after 10 minutes and 30 minutes of reaction, respectively. The concentration of phenol in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0123] Embodiment 15

[0124] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0125] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0126] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0127] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200 ppm of chlorobenzene, wherein the amount of the activated fly ash catalyst added was 400 mg / L and the reaction temperature was 40°C; the adsorption was stirred for 30 minutes, and the concentration of chlorobenzene in the solution was measured; then hydrogen peroxide was added in an amount of 3 ml / L, and the concentration of chlorobenzene in the solution was measured after 10 minutes and 30 minutes of reaction, respectively. The concentration of chlorobenzene in the simulated wastewater was detected by liquid chromatography, and the corresponding adsorption / degradation rate was calculated.

[0128] Example 16

[0129] Step 1: 10 g of fly ash raw material from power plant A, 2.5 ml of ethanol, and 12 g of NaOH were mixed in a ball mill and placed in a ball mill for ball milling (ball milling frequency of 500 Hz, ball milling time of 2.5 h);

[0130] Step 2: further melt-calcining the ball-milled fly ash obtained in step 1 at a temperature of 450° C. for 4 hours;

[0131] Step 3: Wash the solid calcined in step 2 with deionized water until the pH value is close to neutral, and then dry it to obtain an active fly ash catalyst.

[0132] The activated fly ash catalyst obtained as described above was added to simulated wastewater containing 200ppm methylene blue, wherein the amount of the activated fly ash catalyst added was 400mg / L and the reaction temperature was 40°C; the solution was stirred and adsorbed for 30min, and the concentration of methylene blue in the solution was measured; then hydrogen peroxide was added in an amount of 3ml / L, and the concentration of methylene blue in the solution was measured after 10min and 30min of reaction, respectively. The concentration of methylene blue in the simulated wastewater was detected by an ultraviolet spectrophotometer, and the corresponding adsorption / degradation rate was calculated.

[0133] Table 6 Activity data table of Example 1, Example 14 to Example 16

[0134] Example 1 Embodiment 14 Embodiment 15 Example 16 Adsorption rate (30min) 10.4% 12.8% 13.2% 20.2% Degradation rate (10min) 86.3% 16.9% 33.9% 99.3% Degradation rate (30min) 99.6% 99.6% 75.8% 99.7%

[0135] The activity test results in Table 6 above show that the catalyst obtained after fly ash activation is effective in degrading different pollutants. The degradation rates of o-chlorophenol, phenol and methylene blue can reach more than 99.5% after 30 minutes of reaction. Although the effect on chlorobenzene is not so good, the degradation rate can reach 75.8% after 30 minutes of reaction. This shows that the activity of fly ash is greatly improved after alcohol-assisted mechanical ball milling and low-temperature melting, and it is universal for different pollutants.

[0136] Embodiment 17

[0137] The catalyst obtained by calcining in Example 1 was subjected to 4 cycles of degradation experiments. Ortho-chlorophenol was selected as a model chlorine-containing organic pollutant to simulate the degradation of wastewater. The concentration of chlorobenzene was 200ppm, the concentration of the catalyst was 0.4g / L, 40mg of the activated fly ash catalyst was put into 100ml of ortho-chlorophenol aqueous solution to carry out pollutant adsorption-degradation simulation experiment (after adsorption for the first 30 minutes, an oxidant was added for oxidation degradation), and the amount of hydrogen peroxide was 3ml / L. HNO3 was used to adjust the initial pH value of the reaction solution to 3, and the reaction temperature was 40°C.

[0138] Table 7 Activity data table of Example 17

[0139] Run 1 Run 2 Run 3 Run 4 Run 5 Adsorption rate (30min) 2.9% 6.9% 5.0% 5.3% 5.7% Degradation rate (10min) 26.4% 17.0% 12.0% 10.6% 15.1% Degradation rate (30min) 99.0% 97.8% 98.1% 96.0% 94.1%

[0140] Embodiment 18

[0141] The catalyst obtained by calcining in Example 7 was subjected to 4 cycles of degradation experiments. Ortho-chlorophenol was selected as a model chlorine-containing organic pollutant to simulate the degradation of wastewater. The concentration of chlorobenzene was 200ppm, the concentration of the catalyst was 0.4g / L, 40mg of the activated fly ash catalyst was put into 100ml of ortho-chlorophenol aqueous solution to carry out pollutant adsorption-degradation simulation experiment (after adsorption for the first 30 minutes, an oxidant was added for oxidation degradation), and the amount of hydrogen peroxide was 3ml / L. HNO3 was used to adjust the initial pH value of the reaction solution to 3, and the reaction temperature was 40°C.

[0142] Table 8 Activity data table of Example 18

[0143]

[0144] From the results of the cyclic experiments of the catalysts in Examples 1 and 7, it can be seen that the catalyst obtained by ball milling fly ash, ethanol and sodium hydroxide and then low-temperature alkali melting and roasting has higher stability. After 4 cycles, the degradation rate can reach more than 90% after 30 minutes of reaction. However, the stability of the catalyst obtained by direct ball milling and roasting of fly ash and sodium hydroxide is poor. After 4 cycles, the degradation rate after 30 minutes is only 23.4%. This shows that ethanol plays a great role in the activation process of fly ash, which is conducive to the in-situ construction of the active phase.

[0145] The preferred embodiments of the present invention are described above; however, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0146] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0147] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An activated fly ash-based catalyst, characterized in that: The raw materials of the catalyst include fly ash raw material, alkali activator and alcohol, wherein the mass ratio of the fly ash raw material to the alcohol is 0.5-10:1, and the mass ratio of the fly ash raw material to the alkali activator is 0.1-5.0:

1.

2. An activated fly ash-based catalyst according to claim 1, characterized in that: The mass ratio of the fly ash raw material to the alcohol is 2-6:1, and the mass ratio of the fly ash raw material to the alkali activator is 0.1-2:

1.

3. An activated fly ash-based catalyst according to claim 1, characterized in that: The fly ash raw material is industrial waste fly ash from coal-fired power plants.

4. An activated fly ash-based catalyst according to claim 1, characterized in that: The alcohol is a short-chain alcohol, a low-carbon fatty alcohol with 1 to 4 carbon atoms and a combination thereof, including methanol, ethanol, propanol or butanol.

5. The activated fly ash-based catalyst according to claim 1, characterized in that: The alkali activator includes one or more of oxides, peroxides, hydroxides and carbonates of alkali metals and alkaline earth metals.

6. A method for preparing an activated fly ash-based catalyst as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing fly ash raw materials with an alkali activator and alcohol, performing mechanical ball milling, and then performing melt roasting, and washing and drying the obtained product to obtain an active fly ash-based catalyst.

7. The method for preparing an activated fly ash-based catalyst according to claim 6, characterized in that: The mechanical ball milling conditions are as follows: the ball milling frequency is 100-700 Hz, and the ball milling time is 1-5 h; The melt roasting conditions are as follows: the roasting temperature is 200-800°C and the roasting time is 0.5-5h.

8. The method for preparing an activated fly ash-based catalyst according to claim 6, characterized in that: The washing is performed by using deionized water or a dilute acid solution.

9. An application of an activated fly ash-based catalyst as claimed in any one of claims 1 to 5, characterized in that: The catalyst is used to treat wastewater containing organic pollutants.

10. The use of the activated fly ash-based catalyst according to claim 9, characterized in that: The amount of the catalyst added is 100-1000 mg / L; An oxidant is also added during the treatment process, and the oxidant is selected from at least one of hydrogen peroxide, peracetic acid, persulfate, permonosulfate and ozone.

Citation Information

Patent Citations

  • Modified fly ash with adsorption and catalysis functions as well as preparation method and application thereof

    CN109046298A

  • Method for manufacturing fly ash fiber pulp performance modifier

    CN101748649A

  • Method of treating traditional Chinese medicine wastewater by utilizing modified fly ashes and photocatalyst

    CN103613232A

  • Method for preparing heavy-metal wastewater adsorbent based on solid waste modification and utilization

    CN104624151A

  • Fly ash modified adsorbent and preparing method thereof and method of treating oily sewage

    CN104826578A